The dependence insurance (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2013)
Along this work one tries to realize a rigorous and critical analysis of the law of promotion of the personal autonomy and situations of dependence from the point of view of the private assurance. The almost void insurance deprived of the dependence and the bet by a public coverage, amen of the own (proper) psychological resistance to assuring such a contingency, they turn into the principal obstacles for thesuccess of the assurance.
Keywords: Private insurance; dependence; basic acts of the daily life; disability; public coverage